street smart sustainability : the entrepeneur's guide to profitably greening your organization's DNA. - Mager, David, ....-; Sibilia, Joe, ....- (San Francisco : Berrett-Koehler, 2010)
If you run a small to medium-sized business and you're wondering whether or not to go green, this book probably isn't for you. Although David Mager and Joe Sibilia do include ten reasons that sustainability makes economic and ecological sense, they're not here to convince you why. Street Smart Sustainability is about how-detailed, nuts-and-bolts, step by step advice on how to green business green profitably. Read cover to cover this is a comprehensive A to Z handbook, but each chapter also works as a self-contained stand-alone guide to a specific business function. So if you need to you can go right to whichever chapter speaks to your needs at the moment. Mager and Sibilia begin by discussing how to get employee buy-in to and motivate your company into becoming sustainable. Then they cover how to get started-auditing your current sustainability position, developing a plan to move forward, and quantitatively measuring your progress. With a plan and metrics in place, Mager and Sibilia move on to the particulars. They detail how to design products to be sustainable from the get-to, green your facilities, use renewable energy, minimize your carbon footprint, find green vendors to work with, reduce harmful emissions, and recycle waste products. The book is filled with real-world examples from a variety of businesses and industries. The emphasis is always on practicality-besides seasoned advice Mager and Sibilia provide a wide range of tools you can use immediately to implement their suggestions
Keywords: Duurzame ontwikkeling; Ethisch ondernemen; Milieuzorg -- Ondernemingen